Luisa de Borja y Aragón (1520-1560), a figure of authority and erudition in the Renaissance (History Journal «Jerónimo Zurita», 2025)
The exemplary purpose of the hagiographies of Luisa de Borja has conditioned her critical and historiographical reception, associated with the sphere of saintliness. This work explores how the life stories of Luisa de Borja built an image of spirituality based on the successful counter-reformist hagiographical model. In order to contribute to a more nuanced picture, this idealized image is reviewed here by delving into unknown episodes of her life, which highlight her intervention in the political, religious and cultural spheres.
Keywords: Luisa de Borja y Aragón; Borja family; Aragon family; Female Nobility; Female saintliness; Early Modern Women’s Writing; Renaissance